2018
DOI: 10.1002/alr.22181
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain management after sinus surgery: a survey of the American Rhinologic Society

Abstract: Most providers prescribed opioids after FESS. There was no significant difference in the number of opioids prescribed based on geography or practice setting. There was significant heterogeneity in the adjuvant pain management strategy between academic and private practitioners. Most members provided patient education and few reported poor pain control. However, there was a gap in understanding of appropriate medication disposal and evidence-based postoperative pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 25 publications
1
43
1
1
Order By: Relevance
“…Opioid prescription behaviors after ESS have not been well characterized in the literature previously. In a recent survey of American Rhinology Society members, 94% of respondents reported prescribing opioids after ESS . Among those surveyed, mean tablets prescribed was greater than compared to our study cohort (27.4 tablets vs. 15.6 tablets) .…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Opioid prescription behaviors after ESS have not been well characterized in the literature previously. In a recent survey of American Rhinology Society members, 94% of respondents reported prescribing opioids after ESS . Among those surveyed, mean tablets prescribed was greater than compared to our study cohort (27.4 tablets vs. 15.6 tablets) .…”
Section: Discussioncontrasting
confidence: 52%
“…In a recent survey of American Rhinology Society members, 94% of respondents reported prescribing opioids after ESS. 12 Among those surveyed, mean tablets prescribed was greater than compared to our study cohort (27.4 tablets vs. 15.6 tablets). 12 However, there is limited information about variations in prescriber behavior and factors that may influence quantity of opioid prescribed.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Despite these findings, the number of narcotics prescribed remains relatively high and inconsistent between providers. A recent survey querying members of the American Rhinology Society revealed that nearly 94% of otolaryngologists prescribed an opioid prescription following FESS . In a study by Arianpour et al using the Centers for Medicare and Medicaid Services database, researchers found that rhinologists on average prescribed 5.4 days of opioids after FESS, with variations depending on surgeon age, experience, and demographics .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the pain may increase cardiac and pulmonary complications and even lead to death (Gerbershagen et al, 2013;Pöpping et al, 2008). Furthermore, postoperative pain can increase healthcare costs and reduce work productivity (Gray et al, 2018). Although laparoscopy has been widely used in gynaecological surgery, resulting in a smaller incision and less postoperative pain (Gray et al, 2018), pain after laparoscopic gynaecological surgery still remains a problem (Kehlet, 2018).…”
Section: Introductionmentioning
confidence: 99%